Three-dimensional kinematic corridors of the head, spine, and pelvis for small female driver seat occupants in near- and far-side oblique frontal impacts - Humm, John R.; Yoganandan, Narayan; Driesslein, Klaus G.; Pintar, Frank A. (Traffic injury prevention, 2018)
Objectives: Analyses of recent automotive accident data indicate an increased risk of injury for small female occupants compared to males in similar accidents. Females have been shown to be more susceptible to spinal injuries than males. To protect this more vulnerable population, advanced anthropomorphic test devices (ATDs) and computer human body models are being developed and require biofidelity curves for validation. The aim of this study is to generate female-specific 3D kinematic corridors in near- and far-side oblique frontal impacts for the head, spine, and pelvis. Methods: Eight specimens were procured and prescreened for mass, stature, and quantitative computed tomography bone mineral density and preexisting injuries to minimize biologic variability. Sets of 4 noncolinear retroreflective targets were placed on the back of the head; dorsal spine at T1, T8, and L2; and posterior sacrum. Instrumented computed tomography scans were obtained to measure the orientation and position of the markers relative to anatomic fiducials. The specimens were placed on a buck representative of a generic automotive driver's seat environment designed to minimize lower-extremity and pelvic motion. The buck was oriented such that the buck centerline was seated 30° from the impact vector in either a near- or far-side oblique frontal configuration. Preposition of the occupant was specified to the 50th percentile male H-point location, thigh and tibial angles, and torso angle. Impact was delivered via a servo-acceleration sled to the base of the buck with a 30 km/h 9 g trapezoidal pulse. Occupants were restrained by a standard 3-point belt that had a custom load-limiter device set to 2 kN at the D-ring side of the shoulder belt. Target motion was recorded at 1 kHz using a 3D optical motion capture system. Anatomic motion of the head, spine, and pelvis was calculated relative to the seat, and the average response was determined from 4 near-side and 4 far-side tests. The borders of the corridor were determined by calculating a standard deviational ellipse in the x, y, and z planes at each time step. Results: Plots of the biofidelity corridors for near- and far-side tests are shown in planes parallel to the seat from the lateral, rear, and overhead directions. Averaged peak excursions in the fore/aft and lateral directions are compared for the near- and far-side corridors. Near-side female and male tests are similarly compared. Conclusions: In general, average peak excursions were greater in the far-side configuration than in the near-side configuration. Peak excursion results compared well with similar tests conducted on male postmortem human subjects (PMHS). The kinematic corridors developed in the current study serve as a set of biofidelity corridors for the development of current and future physical and computational surrogates.